2018
DOI: 10.1002/aqc.2908
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA short tandem repeats unveil hidden population structuring and migration routes of an endangered marine turtle

Abstract: The assessment of the composition and dynamics of endangered populations is crucial for management and conservation, and appropriate genetic markers are critical. The genetic structuring of the Mediterranean green turtle (Chelonia mydas) populations and the origin of the stranded animals found along the Israeli coast was investigated using new highly polymorphic short tandem repeat (STR) markers. The structuring of nesting populations was studied using pairwise genetic distances and a principal coordinates ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Our results demonstrate that, by analysing only a small number of families, we have recovered 11 out of 16 haplotypes previously reported for the whole population of Israel 30 . Furthermore, considering a previous comprehensive study in nesting females in the Mediterranean and that all our samples are from Israel, we have reported 25 new haplotypes for the Israeli population.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Our results demonstrate that, by analysing only a small number of families, we have recovered 11 out of 16 haplotypes previously reported for the whole population of Israel 30 . Furthermore, considering a previous comprehensive study in nesting females in the Mediterranean and that all our samples are from Israel, we have reported 25 new haplotypes for the Israeli population.…”
Section: Discussionsupporting
confidence: 67%
“…Consequently, most phylogenetic and phylogeographic studies have ignored the minor haplotypes indicated by additional peaks, Table 1. Samples were grouped according to the clusters detected in www.nature.com/scientificreports www.nature.com/scientificreports/ or at most reported it but did not use them for subsequent analysis 28,30 . Using HTS, we were able to investigate the whole population of mtDNA molecules composing an individual's haplotypic profile by analyzing the repeat region of the mtDNA D-loop of green sea turtles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations